MLP SAĞLIK HİZMETLERİ ANONİM ŞİRKETİNİN FİNANSAL PERFORMANSININ ÜÇ FARKLI YÖNTEM İLE ANALİZİ - (:unkn) unknown (My University, 2020)
Bu çalışma borsada işlem görmekte olan MLP Sağlık Hizmetleri A.Ş.’nin (MLP Care) finansal tablolarının retrospektif olarak analizini yaparak, mevcut finansal performansını değerlendirmeyi ve literatüre katkı sağlayarak farklı finansal analiz yöntemlerini bir arada görebilmeyi amaçlayan betimleyici bir araştırmadır. Çalışma, ilgili işletmenin 2016, 2017 ve 2018 yılı bilanço ve gelir tabloları ele alınarak yürütülmüştür. İşletmenin ilgili yıllara ait finansal tabloları karşılaştırmalı (yatay) analiz, yüzde yöntemi (dikey) ile analiz ve trend analizi ile değerlendirilmiştir. Verilerin analizinde M.S. Office Excel programı kullanılmıştır. Yapılan finansal analizler sonucu; işletmenin kendisini yüksek oranda yabancı kaynaklarla finanse etmekte olduğu görülmüştür. Aşırı borçlanmayla birlikte özellikle 2018 yılında karşılaştığı finansman giderleri işletmenin zarara girmesinin temel etkeni olarak görülmektedir. Bu etkenlerden dolayı finansal açıdan zorluklarla karşı karşıyadır. Bu durumu önlemek için özellikle borçlanma finansman giderleri ve kur farklarını azaltmaya yönelik politikalar gibi gider kalemlerini azaltacak önlemler belirlemesi önerilebilir.

1. LITERATURE Today, technological change and development in health services, aging population, increasing chronic diseases and demand cause serious financial problems for healthcare providers. For these reasons, it is beneficial for health companies to evaluate their financial performance correctly and to make their financial plans accordingly, in order to cope with financial sustainability problems, which can be seen all over the world in health area (Janati et al., 2014). Financial statement analysis, which is one of the financial performance evaluation methods, is a management accounting sub-system aiming to examine the financial structure of hospital enterprises and to direct future decision making in the management of hospitals (Özgülbaş, 2009). By analyzing the strengths and weaknesses of the enterprises, financial analyzes enable healthy and rational plans and policies towards their future. In order to provide the expected benefit from financial analysis, it is often necessary to use more than one technique together rather than a single analysis technique (Aydın et al., 2015). This study aims to retrospectively analyze the financial statements of MLP Health Services Corporation (MLP Care) which is the largest Turkish private healthcare group and traded on the stock exchange, to evaluate the current financial performance and to see different financial analysis methods together by contributing to the literature. 2. DESIGN AND METHOD 3. FINDINGS AND DISCUSSION The study was carried out by considering the 2016, 2017 and 2018 balance sheets and income statements of the relevant company in descriptive research type. The related tables have been obtained from the financial reports of Health Services Inc. and independent auditor's reports. The financial statements of the company for the relevant years were evaluated by comparative (horizontal) analysis, vertical analysis and trend analysis. In the analysis of the data, M.S. Office Excel program was used. As a result of the financial analysis; It has been observed that the enterprise finances itself with a high proportion of foreign funds. It is noteworthy that the own resources of the business decreased by 60.5 percent in 2017 compared to 2016, followed by a large increase of 117% in 2018. This increase is thought to have occurred as a result of the public offering of the enterprise at the beginning of 2018. However, despite this increase in capital, the enterprise is at a loss in 2017 and 2018. It is seen that the financial expenses of the enterprise have a great effect on this loss. In the annual report of the company, it was stated that the loss of 104 million TL was caused by the foreign exchange loss of 245 million TL (including the exchange fixing expense) and 464 million TL of financial expenses. The Company has used 600 million TL of the revenues from the capital increase in public offering in the payment of its financial debts (MLP Care Annual Report, 2018). Thus, it is aimed to reduce the financing expenses and foreign exchange loss arising from the said debts. In addition, the entity stated that the total principal and interest payable to be paid in the period of 2019-2020 (72 million Euros in total) fixed the exchange rate for 56 million Euros (MLP Care Annual Report, 2018). 4. CONCLUSION, RECOMMENDATION AND LIMITATIONS As a result, despite the increasing tendency of sales and gross income of the enterprise, it can be said that it faces financial difficulties due to financing costs such as exchange differences and interest expenses for its current situation. It is a risk factor for the business to finance itself with a high level of foreign resources. In case of a crisis, measures should be taken to avoid financially difficult days. The enterprise is expected to set precautions and policies to reduce the expense items. As a matter of fact, the fact that the enterprise fixes the exchange rate in interest debt payments for the 2019-2020 period and that the company can strengthen its financial structure and profit-making capacity with the public offering revenues indicates that it has taken measures for the future periods and the financing situation will improve. Limitations: It can be said as a limitation of the study that the financial performance analysis is not
ANALYSIS OF THE FINANCIAL PERFORMANCE OF MLP HEALTHCARE CORPORATION BY THREE DIFFERENT METHODS